2018
DOI: 10.1097/pai.0000000000000519
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Multicolor Flow Cytometry and Immunohistochemistry for the Detection of Disseminated Tumor Cells

Abstract: Disseminating cells of a primary solid tumor may represent the origin of metastases and relapses. We aimed at comparing the diagnostic efficacy of multicolor flow cytometry (MFC) and morphology/immunohistochemistry (IHC) in the detection of disseminated tumor cells in the bone marrow (BM) and body fluids of patients with solid tumors, and in pediatric neuroblastoma cases. We investigated 72 samples retrospecively from 50 patients by MFC. Morphology/IHC data were available in 48 cases. In the first cohort, 36 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…First, CD11b immunohistochemistry on paraffin-embedded sections has been shown to produce variable results based on processing and storage conditions [15, 16]. Second, immunohistochemistry has been argued to be inferior to flow cytometry for analysis of some cell types in tumors [17]. We also found that the percentage of cells in NFPAs that were CD11b + did not vary regionally between the medial versus lateral aspects of the tumor (Figure 1C; Supplementary Figure 2), further validating the choice of this approach.…”
Section: Resultsmentioning
confidence: 99%
“…First, CD11b immunohistochemistry on paraffin-embedded sections has been shown to produce variable results based on processing and storage conditions [15, 16]. Second, immunohistochemistry has been argued to be inferior to flow cytometry for analysis of some cell types in tumors [17]. We also found that the percentage of cells in NFPAs that were CD11b + did not vary regionally between the medial versus lateral aspects of the tumor (Figure 1C; Supplementary Figure 2), further validating the choice of this approach.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, in 2013, we evaluated the (potential) clinical utility of a comprehensive MFC panel of 32 markers for the diagnostic orientation and classification of pediatric solid tumors, based on a limited series of 52 samples from 40 patients suspicious of pediatric cancer [ 22 ]. The panel of markers evaluated in this preliminary study showed high diagnostic accuracy (96%) vs. conventional histopathology [ 22 ], supporting the great potential of MFC to detect tumor cells in pediatric non-Hodgkin (NHL) [ 23 , 24 ] and Hodgkin lymphoma (HL) [ 25 ], RMS [ 26 ], NBL [ 26 , 27 ], and carcinomas [ 28 , 29 ]. In turn, this study also revealed the limited utility and potential redundancy of several markers, together with the need for additional stainings for improved diagnosis of several specific tumor subtypes [ 22 ], that should be combined into a single multicolor antibody combination for screening purposes.…”
Section: Introductionmentioning
confidence: 68%
“…This is in contrast with the findings by Mishra et al (67), who did not observe significant differences in eosinophils numbers in the GI of SPF and GF mice when quantified by histology. Several factors might have contributed to this discrepancy including the strain of mice (Black Swiss mice vs. C57BL/6 and BALB/c), microbiome differences under SPF conditions, the number of mice utilized in each study (n = 5 vs. n = 12-20) and, lastly, the technique employed for eosinophils quantification, as it is likely that flow cytometry allowed for a more comprehensive and precise quantification than immunohistochemistry using the eosinophil granule protein, major basic protein (MBP) (68). Importantly, we show that intestinal eosinophils in GF mice contain granules of smaller size and less cytoplasmic granule content than SPF controls, which may lead to eosinophil underdetection when using MBP-based methods.…”
Section: Discussionmentioning
confidence: 99%